Generating Electricity Using Microbial Fuel Cell Powered by Benthic Mud Collected From Two Locations in Akure, Nigeria - D. V, Adegunloye; T. M, Olotu (European Scientific Journal, ESJ, 2017)
Generating electricity using microbial fuel cell powered by benthic mud collected from two locations in Akure was carried out. The locations were Riverbed of FUTA and Apatapiti area of Akure. This was achieved by building anode and cathode containers connected together by a salt bridge and an external circuit was made to transfer the electrons from the anode to the cathode. Bacteria and fungi were isolated from the benthic mud for eight days using standard microbiological techniques. Lactobacillus plantarum, Escherichia coli, Bacillus subtilis, Enterobacter aerogenes, Trichoderma sp, Mucor sp and Alterania sp; Lactobacillus plantarum, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Myrothecium sp and Geotrichum candidum were bacteria and fungi isolated from the benthic mud of Apatapiti area and Riverbed of Futa, Akure respectively. This was used for the generation of electricity using unsterilized mud sample and the control setup was sterilized mud from same source. The set-up was monitored every 24hrous to determine the voltage and current generated. The pH, concentration and temperature were measured. The temperature remains constant throughout the experiment. The set-up were operated at a normal temperature of 27oC and 29oC for Riverbed of FUTA and Apatapiti area of Akure respectively. The peak voltage was between 182.5V and 192.5V and current produced from the main set-up was between 0.3A to 0.53A for Futa river bed while for Apatapiti area of Akure the peak voltage and current were 192.5V and 0.3A respectively. Higher microbial population, current and voltage were observed to be generated in River bed of Futa than Apatapiti area. The difference in the voltage and current and the control set-up shows that anaerobic microorganisms are capable of producing electricity from microbial fuel cell under appropriate conditions.